The Future of Hospitality Management Programs: A Wakeup Call. (November 2020) - Dev, Chekitan S.
Since the founding of Cornell's Hotel School—the world's first, and arguably the finest, collegiate hospitality management program—almost 100 years ago, hospitality management programs have served millions of students and executives worldwide and turned what was simply an occupation into a profession. Our programs are now in jeopardy of declining and ultimately becoming irrelevant. To secure our future, we must deal immediately and effectively with the threats to our existence and seize the opportunities to strengthen our programs. In this article, I present 10 trends that foretell the future decline of hospitality management programs and offer some suggestions to reenergize hospitality management education, research, and engagement.